Comparative transcriptional survey between laser-microdissected cells from laminar abscission zone and petiolar cortical tissue during ethylene-promoted abscission in citrus leaves - Agustí, Javier; Merelo, Paz; Cercós, Manuel; Tadeo, Francisco R.; Talón, Manuel (2017)
Background: Abscission is the cell separation process by which plants are able to shed organs. It has a great impact on the yield of most crop plants. At the same time, the process itself also constitutes an excellent model to study cell separation processes, since it occurs in concrete areas known as abscission zones (AZs) which are composed of a specific cell type. However, molecular approaches are generally hampered by the limited area and cell number constituting the AZ. Therefore, detailed studies at the resolution of cell type are of great relevance in order to accurately describe the process and to identify potential candidate genes for biotechnological applications. Results: Efficient protocols for the isolation of specific citrus cell types, namely laminar abscission zone (LAZ) and petiolar cortical (Pet) cells based on laser capture microdissection (LCM) and for RNA microextraction and amplification have been developed. A comparative transcriptome analysis between LAZ and Pet from citrus leaf explants subjected to an in-vitro 24 h ethylene treatment was performed utilising microarray hybridization and analysis. Our analyses of gene functional classes differentially represented in ethylene-treated LAZ revealed an activation program dominated by the expression of genes associated with protein synthesis, protein fate, cell type differentiation, development and transcription. The extensive repertoire of genes associated with cell wall biosynthesis and metabolism strongly suggests that LAZ layers activate both catabolic and anabolic wall modification pathways during the abscission program. In addition, over-representation of particular members of different transcription factor families suggests important roles for these genes in the differentiation of the effective cell separation layer within the many layers contained in the citrus LAZ. Preferential expression of stress-related and defensive genes in Pet reveals that this tissue is likely to be reprogrammed to prevent pathogen attacks and general abiotic stresses after organ shedding. Conclusion: The LCM-based data generated in this survey represent the most accurate description of the main biological processes and genes involved in organ abscission in citrus. This study provides novel molecular insight into ethylene-promoted leaf abscission and identifies new putative target genes for characterization and manipulation of organ abscission in citrus.